أهمية الجباية المحلية في تعزيز الاستقلالية المالية لتسيير ميزانية الجماعات المحلية "البلدية" - لخضر، عبيرات (جامعة عمار ثليجي الأغواط - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2018)
قد ترسخ الاهتمام بجدوى نظام اللامركزية الإدارية بأبعادها المختلفة، من خلال وجود قناعات تشير إلى ضرورة تبني أجهزة وهيئات أخرى تقف بجانب الحكومة المركزية نظرا لتزايد مهامها واختصاصاتها في شتي الميادين والمجالات، وبالتالي كان من الضروري توزيع المهام والاختصاصات بين الحكومة والهيئات المحلية، الأمر الذي يؤدي إلى تخفيف العبء عن كاهل السلطة المركزية، لذلك تم تفويض ونقل بعض السلطات والاختصاصات إلى الهيئات المحلية فيما يتعلق بالبعد الإداري، وفى نفس الإطار كان تركيز العديد من دول العالم على اللامركزية المالية، باعتبار أن توافر الموارد المالية المحلية الذاتية يساعد على دعم الاستقلالية المالية للجماعات المحلية، بحيث يتعين أن تكون لديها مصادر للتمويل (الجباية المحلية) ومدى مساهمة هذه الموارد المالية في تمويل الميزانية المحلية وتأثيرها في استقلالية الجماعات المحلية وحريتها في العمل ومدى إمكانية مبادرتها بالتخطيط لمشروعات التنمية المحلية.
The interest of the administrative decentralization system can be established in its different dimensions, through the existence of convictions indicating the need to adopt other plans and bodies which stand alongside the central government due to the progressive growth of its functions in various fields and sectors, Consequently, it was necessary to distribute tasks and competences between the government and the local authorities, thus reducing the load of the central authority, for this, certain powers and competences were delegated local authorities with regard to the administrative dimension. In the same context, many countries in the world have focused on financial decentralization by considering that the availability of national financial resources helps to support the financial autonomy of local authorities by having the sources of funding (local taxation) and the scale of the contribution of these financial resources to the financing of the local budget, and its impact on autonomy, the freedom of local communities in work as well as the extent of the possibility of undertaking the initiative to plan local development projects.
Keywords: الإدارة الضريبية -- التنمية المحلية -- اللامركزية الإدارية -- الموارد المالية